Kedudukan Wali Fasik Dalam Akad Nikah Menurut Fiqh Klasik Dan Relevansinya Dengan Praktik Perkawinan Kontemporer - Widia Usada; Muhammad Amar Adly (Al-Muqaranah : Jurnal Perbandingan Hukum dan Mazhab, 2026)
This study aims to analyze the position of the fasik guardian in the validity of marriage contracts according to classical fiqh and examine its relevance to contemporary marriage practices in Indonesia. The background of this study is based on the tension between the normative provisions of classical fiqh, which require the guardian to be just, and the social reality of modern society, where the guardian still often plays a role in marriage contracts that are performed and recorded by the state. This study uses a qualitative method with a legal-normative approach through a literature study of classical fiqh books, particularly the book Fathul Mu'in bi Syarhi Qurratil 'Ain, as well as contemporary Islamic legislation and legal literature. The results show that in classical fiqh, a fasik guardian does not, in principle, meet the requirements of justice, so that his guardianship is disputed among scholars, but repentance is seen as being able to erase fasik and restore guardianship rights under certain conditions. Furthermore, the concept of a fasik guardian in classical fiqh remains normatively relevant in contemporary marriage practices, but requires a contextual approach to be in line with the marriage registration system and the need for legal certainty and public interest in Indonesia.Keyword: Classical fiqh, Contemporary marriage, Legal certainty, Marriage contract, Fāsiq guardian